2012
DOI: 10.1259/bjr/76424694
|View full text |Cite
|
Sign up to set email alerts
|

Interobserver delineation variation in lung tumour stereotactic body radiotherapy

Abstract: The interobserver delineation variation was very small in this systematic cross-sectional analysis, although significantly larger in the CC direction than in the transversal plane, stressing that anisotropic margins should be applied. This study is the first to make a systematic cross-sectional analysis of delineation variation for peripheral lung tumours referred for SBRT, establishing the evidence that interobserver variation is very small for these tumours.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 24 publications
2
27
0
Order By: Relevance
“…MLC tracking plans utilised the end-of-exhale phase as a reference phase to define the GTVTracking, with the CTV defined as being equal to the GTV and a 5 mm CTV to PTV margin. The end-of-exhale phase assures a proper localisation and delineation of the tumour [17][18][19] while the 5 mm margin has been described in the literature to be sufficient to account for tracking system latency up to 500 ms [20] and differences in tumour sizes and shape during respiration [21]. The exhale phase CT scan is likely to have the fewest imaging artefacts, and having the smallest lung volume, is likely to over-, rather than under-estimate the actual lung dose.…”
Section: Mlc Tracking With Electromagnetic-guidancementioning
confidence: 99%
“…MLC tracking plans utilised the end-of-exhale phase as a reference phase to define the GTVTracking, with the CTV defined as being equal to the GTV and a 5 mm CTV to PTV margin. The end-of-exhale phase assures a proper localisation and delineation of the tumour [17][18][19] while the 5 mm margin has been described in the literature to be sufficient to account for tracking system latency up to 500 ms [20] and differences in tumour sizes and shape during respiration [21]. The exhale phase CT scan is likely to have the fewest imaging artefacts, and having the smallest lung volume, is likely to over-, rather than under-estimate the actual lung dose.…”
Section: Mlc Tracking With Electromagnetic-guidancementioning
confidence: 99%
“…Guidelines for margin calculation are also given, based on relevant literature. [57][58][59][60][61][62][63] In the Danish guidelines, there are no recommendations regarding respiratory gating, breath-hold or motion tracking. None of these techniques are used on a routine basis, although they may be applied in some clinics for specific cases where normal tissue constraints or target dose prescription cannot otherwise be achieved.…”
Section: Clinical Protocolsmentioning
confidence: 99%
“…8,11,13,[23][24][25] A recent study suggested that delineation variation may be smaller in peripheral lung tumors referred for SBRT in a single-institutional setting. 26 In all these studies, participants delineated structures on a common radiological data set, and interobserver variation was quantified using various parameters involving distribution of volumes, overlap between contoured volumes, and statistical measures of agreement. 8,11,13,[23][24][25] Previous studies have not investigated whether contour variations had a meaningful influence on dose distribution.…”
Section: Discussionmentioning
confidence: 99%